Wpływ dwujęzyczności na kształtowanie się urzędowej odmiany języka – na przykładzie średniowiecznych wielkopolskich rot sądowych - Słoboda, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article discusses Polish-Latin bilingualism of Polish medieval legal texts and its impact on the shaping of the official language variant. The article presents constructions that, in their own structure of court oath, include a form of set and often repeated formulas. These are: the formula of initial oath (Tako mi pomoży Bog i święty krzyż [so help me God and the holy cross]) and the comparative construction indicating the membership of a social class of the participants of the events (tako dobry jako sam [as good as himself]) or the material value (tako dobry jako [as good as]). These constructions would appear in the Polish text in Latin, both in full or shortened form, or they would be part in Polish, part in Latin. The stable form of constructions that appeared in Latin as calques due to the influence of Polish indicates that they became, as a result of the domination of the Latin template, vivid markers of the official style in medieval Polish.